The Use of Game-Based Learning Assisted by Zep Quiz to Improve Students’ Interest and Motivation in Mathematics Learning - Aisha Shakila Yasmin; Budi Murtiyasa (Journal of Educational Sciences, 2026)
Low interest and motivation in mathematics learning remain challenges because they can reduce students’ engagement and participation in classroom activities. This study aimed to describe students’ initial learning interest and motivation, examine the implementation of Game-Based Learning (GBL) assisted by Zep Quiz, and determine its improvement across learning cycles. The study employed Classroom Action Research based on the Kemmis and McTaggart model and was conducted in two cycles involving 33 eleventh-grade students at SMA N 1 Kartasura. Data were collected through questionnaires, observations, and documentation. Quantitative data were analyzed descriptively using means, percentages, and relative improvement, while qualitative data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that learning interest increased from 67.73% in the pre-cycle to 87.30% in Cycle II, equivalent to a 28.90% relative increase. Learning motivation increased from 67.36% to 88.85%, with a 31.90% relative increase. Student activity also increased from 80.77% in Cycle I to 94.23% in Cycle II. These findings indicate that GBL assisted by Zep Quiz effectively improved students’ interest, motivation, and classroom engagement in mathematics learning.